ANALISIS SEKTOR UNGGULAN PEREKONOMIAN DI KABUPATEN/KOTA DENPASAR, BADUNG, GIANYAR, DAN TABANAN - Putra, Putu Indra Perdana; Yadnya, I Putu (E-Jurnal Manajemen; Vol 7 No 10 (2018)DO - 10.24843/EJMUNUD.2018.v07.i10.p16, 2018)
The determination of the regional leading sector is very important as the basis in the development planning and improvement of the economy of a region. The purpose of this study is to determine the sectors that become the leading sector of the economy in the regencies / cities in the region Sarbagita, so researching in the regencies / cities in the region Sarbagita. The population and sample used are 17 sectors according to business field in GRDP 2014-2016, and the method of determining the sample is census. This research uses data analysis technique of Klassen Tipology, LQ, and Overlay. Based on the results of research that became the leading sectors in the Sarbagita region are the major trade and retail sectors, the financial services and insurance sector, and the education services sector. the sector of accommodation and drinking, the information and communications sector, the processing industry sector, as well as the government administration, defense and social security sectors. In the future each local government should be able to maintain the stability of growth of the leading sectors, because the superior sector is the strength and competitiveness of regions in improving the regional economy. Keywords: leading sector, klassen tipology, LQ, overlay